Actores, escenarios y relaciones sociales en tres publicaciones periódicas mexicanas de mediados del siglo XIX - Pérez Benavides, Amada Carolina (El Colegio de México, A.C., 2007)
This paper  analyzes  the literature  and illustrations of manners published  in three nineteenth-century Mexican  periodicals,  in order to reveal the role of these texts and images in the construction  of national  identity.  Following  this analytical line, the author  explores  how  the  viewpoint  of the  literature  of manners was born and the traits it acquired specifically during the 1850's, when the representation of Mexicans seems to have gone though its most  important transition:  from local and regional types to national archetypes.